The Labor Guide to Retirement Plans : For Union Organizers and Employees - Russell, James W., 1944- (Book collections on Project MUSE., 2021)
"Researching retirement plans should not take the rest of your life, even if deciphering the relevant paperwork seems to have become a full-time job. Deliberately elaborate legalese is obscuring the efforts of financial elites to seize control of workers' collective retirement savings-and The Labor Guide to Retirement Plans is here to translate. In theory our national pension system, Social Security, should function well as a form of social insurance delivering partial retirement security, while workplace 401(k)s provide the rest. The problem is that very few do. Indeed, most workers have weak workplace retirement plans if they have them at all-and about half do not. Neoliberal retirement reforms have made matters worse, accelerating financial elites' efforts to replace workers' guaranteed pension plans with weak 401(k)-like savings accounts and stock market investment schemes and ultimately enabling financial elites to seize control of workers' collective retirement savings. The result is arguably the largest source of labor value expropriation over the last four decades. In light of all this, what do workers need to know as they assess their future prospects-especially in terms of the security their retirement plans may or may not bring? What should union activists keep in mind as they push for the national and workplace reforms needed to produce greater retirement security? This nuts-and-bolts book provides a much-needed demystification of the retirement system. Even more than that The Labor Guide to Retirement Plans enables us to take charge of our own personal futures, as a first step towards taking back what belongs to us all"--